In vitro propagation of the endangered orchid Dendrobium chryseum Rolfefrom protocorms culture - Maharjan, Sabitri; Thakuri, Laxmi Sen; Thapa, Bir Bahadur; Pradhan, Shreeti; Pant, Krishna K.; Joshi, Giri P.; Pant, Bijaya (Nepal Journal of Science and Technology, 2020)
The immature seeds of Dendrobium chryseum, a sympodial epiphytic orchid with yellow flowers, were cultured in vitro, and the resultant protocorms were used as explants for seedling development. Protocorms were cultured on ½ MS medium fortified with Kinetin (Kn), 6-Benzylaminopurine (BAP), and Gibberellic Acid (GA3) in three concentrations (0.5mg/L, 1.0 mg/L and 2.0 mg/L) both alone and supplemented with 5% and 10% coconut water (CW). The highest number of shoots of D. chryseum developed on ½ - MS medium fortified with 2.0 mg/L of Kn and 10% CW and the longest shoots developed on ½ MS media fortified with 1.0 mg/L GA3, and 10% CW. The shoot derived from protocorms were placed in ½ MS medium fortified with three different rooting hormones, Indole -3- acetic acid (IAA), Indole -3-butyric acid (IBA) and α-Naphthalene acetic acid (NAA) in different concentrations alone as well as with each 1.0 mg/L hormone combined with 10% CW. The most effective of these media was ½ MS medium fortified with 1.5 mg/L IAA for rooting as well as for the production of longest roots. The present study could be useful for standardizing the protocol for mass propagation of the endangered orchid Dendrobium chryseum.